Autocuidado del pie diabético en el primer nivel de atención - Rojas Girón, Doménica Paola; Tenemaya Uzho, Evelyn Katherine; Paccha Tamay, Carmen Liliana (My University, 2021)
Introduction: Diabetes mellitus represents a high rate of morbidity worldwide and among its complications the diabetic foot, one of the most frequent, representing an incidence of 20% in the population, affecting mainly the elderly. Objective: the purpose of the research was to analyze the self-care of the diabetic foot in the first level of care. Methods: A descriptive, quantitative, crosssectional and non-experimental study was carried out. 46 patients with a diagnosis of diabetic foot participated, with a precision of 5%, a confidence level of 95% and a reliability of Cronbach's alpha 0.984. The data processing was carried out in a database and the statistical analysis in the SPSS version 25 program. The Microsoft Excel 2010 program was used to prepare the tables. Results: The data obtained suggests that 43.5% of the respondents they belong to the group of 61 to 70 years of age; the male sex predominated in a significant way with 56.5% compared to the female 43.5%; 32.6% of the patients carry out household activities and 28.3% engage in informal commerce. 30.4% of users receive guidance on the disease from the nursing staff almost always; the level of pharmacological adherence is 37% and 10.9% does not comply; 32.6% have glucose control and 30.4% perform correct foot hygiene. Conclusions: It is concluded that the nursing staff must strengthen their knowledge so that their interventions are effective and focus on improving the quality of life of patients
Introducción: La diabetes mellitus representa un alto índice de morbilidad a nivel mundial y entre sus complicaciones el pie diabético, uno de los más frecuentes representando una incidencia del 20% en la población, afectando mayoritariamente a los adultos mayores. Objetivo: el propósito de la investigación fue analizar el autocuidado del pie diabético en el primer nivel de atención. Métodos: Se realizó un estudio descriptivo, cuantitativo, transversal y no experimental, participaron 46 pacientes con diagnóstico de pie diabético, con una precisión del 5%, nivel de confianza del 95% y fiabilidad de alfa de Cronbach 0.984. El procesamiento de datos se efectuó en una base de datos y el análisis estadístico en el programa SPSS versión 25, para la elaboración de tablas se usó el programa Microsoft Excel 2010. Resultados: Los datos obtenidos sugieren que el 43,5% de los encuestados pertenecen al grupo de 61 a 70 años de edad; predominando de manera significativa el sexo masculino con 56,5% frente al femenino 43.5%; el 32,6% de los pacientes realizan actividades del hogar y el 28,3% se dedican al comercio informal. El 30,4% de usuarios reciben orientaciones sobre la enfermedad por parte del personal de enfermería casi siempre; el nivel de adherencia farmacológica es del 37% y 10,9% no lo cumple; el 32.6% lleva un control de la glucosa y 30,4% realiza correcta higiene de los pies. Conclusiones: Se concluye que el personal de enfermería debe fortalecer sus conocimientos para que sus intervenciones sean efectivas y se enfoquen en mejorar la calidad de vida de los pacientes
Keywords: PIE DIABETICO; AUTOCUIDADO; ENFERMERIA